Utilization of Iodinated SpaceOAR Vue™ During Robotic Prostate Stereotactic Body Radiation Therapy (SBRT) to Identify the Rectal–Prostate Interface and Spare the Rectum: A Case Report - Conroy, Dylan; Becht, Kelly; Forsthoefel, Matthew; Pepin, Abigail N.; Lei, Siyuan; Rashid, Abdul; Collins, Brian Timothy; Lischalk, Jonathan W.; Suy, Simeng; Aghdam, Nima; Hankins, Ryan Andrew; Collins, Sean P. (Frontiers in Oncology, 2021)
We describe the utilization of SpaceOAR VueTM, a new iodinated rectal spacer, during Robotic Stereotactic Body Radiation Therapy (SBRT) for a Prostate Cancer Patient with a Contraindication to Magnetic Resonance Imaging. A 69-year-old Caucasian male presented with unfavorable intermediate risk prostate cancer and elected to undergo SBRT. His medical history was significant for atrial fibrillation on Rivaroxaban with a pacemaker. He was felt to be at increased risk of radiation proctitis following SBRT due to the inability to accurately contour the anterior rectal wall at the prostate apex without a treatment planning MRI and an increased risk of late rectal bleeding due to prescribed anticoagulants. In this case report, we discuss the technical aspects of appropriate placement and treatment planning for utilizing SpaceOAR VueTM with Robotic SBRT.